Design and Building Assessment Application of Student Learning Outcomes Using Curriculum 2013 WEB Based - Atmaja, Bhagus Sugamayana Dwi; Jusak, Jusak; Santoso, Rudi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Student learning outcomes that effective and efficient can help ease the performance of the school, therefore a system capable of handling the process of assessing student learning outcomes. The assessment system of student learning outcomes is expected to help simplify the performance of the school. The problems that exist in SMA Kartika IV-3 Surabaya is how to design and build the application of student learning outcomes are structured and centralized. Currently, when the teacher will enter the student score, the teacher will enter the student score by using Microsoft Excel application, in recording of the student score it causing error by too many files created in assessing student learning outcomes, each file can be changed by all parties, so the student score data becomes invalid to be incorporated into student report cards. Based on the descripted problems, it is needed an application that can be used to assist the admin and teachers in facilitating the process of student learning outcomes in SMA Kartika IV-3 Surabaya. The solution is making a computerized application that can processing the student learning outcomes at SMA Kartika IV-3 Surabaya, so as teachers inputing student score, the teacher does not need to make various Excel file, and the score can be directly seen by the student.